Perancangan Kawasan Wisata Anime Center Dengan Tema Metafora Di Gedebage, Bandung. - Burhan Luthfi Primawan; Putri Suryandari (MAESTRO, 2019)
Anime Center Tourism Area is a center for information and tourism facilities for anime or modern Japanese culture. In the Anime Center Tourist Area there are anime museums, learning areas, game centers, restaurants, retail stores, and other supporting facilities. Anime Center Tourism is one of the facilities that can accommodate the Japanese modern cultural community in Indonesia. Not only limited to seeing the end can also find out modern Japanese culture, especially anime, manga, cosplay and some foreign animation. The Anime Center Tourist Location in Gedebage Bandung is very appropriate because the evidence of the great enthusiasm of modern Japanese culture is the frequent Japanese events or Matsuri and Bunkasai in this city. An area with a function as a tourist requires an attractive building in terms of visuals. The use of metaphorical themes in building design is considered capable of displaying its own charm, because metaphor is a theme of architectural design that gives the architectural freedom of imagination in architectural design. In accordance with the Aniem Center Tourism Area, the inside is full of extraordinary works of imagination.